The long shadow of history: Roman legacy and economic development - evidence from the German limes - Fabian Wahl (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2015)
This paper contributes to the understanding of the long-run consequences of Roman rule on economic development. In ancient times, the area of contemporary Germany was divided into a Roman and non-Roman part. The study uses this division to test whether the formerly Roman part of Germany show a higher nightlight luminosity than the non-Roman part. This is done by using the Limes wall as geographical discontinuity in a regression discontinuity design framework. The results indicate that economic development - as measured by luminosity - is indeed significantly and robustly larger in the formerly Roman parts of Germany. The study identifies the persistence of the Roman road network until the present as an important factor causing this development advantage of the formerly Roman part of Germany both by fostering city growth and by allowing for a denser road network.
urn:nbn:de:bsz:100-opus-11188
Keywords: N13; N73; O18; R12; R40; 330; Roman Empire; Economic Development; Germany; Boundary Discontinuity; Transport Infrastructure; Persistence